Analisa Karakteristik Lalu – Lintas Pada Jalan Sematang Borang Kota Palembang - Chandra Adi Tama; Pujiono Pujiono; Robi Sahbar (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Sematang Borang Street is a city road frequently used by Palembang residents to reach their homes. Over time, the number of residents in various housing complexes and settlements continues to increase. The flow of vehicles passing through Sematang Borang Street also increases. This increase has the potential to cause transportation problems, such as congestion, decreased road performance, and reduced road user comfort. Therefore, this researcher conducted an analysis to determine the relationship between traffic flow characteristics, such as volume, speed, and capacity, on Sematang Borang Street, in order to address potential future problems. In this study, the author addresses the analysis of traffic characteristics on Sematang Borang Street in Palembang City. The survey was conducted on a weekday using a one-day enumeration method, including vehicle volume and speed surveys. The calculation and analysis revealed a traffic volume of 1,678.7 passenger car units/hour, with a capacity of 1,414.96 passenger car units/hour. The current value of free flow speed is 32.825 km/hour.